Hearth of Budapest: a representative gateway: Renewal of Károly road, Astoria junction, Deák Ferenc square, Bajcsy-Zsilinszky road, József Attila street and adjoining public spaces - Fekete, Albert; Koszorú, Lajos; Zöldi, Péter (4D Journal of Landscape Architecture and Garden Art, 2009)
As an organic part of úrban planning, Gordon Cullen calls open space design “the art of relationship”. The task thus becomes the discovery and potential reinforcement of new, hitherto hidden relationships, which increase and mark the gateway character, creating a predominantly visual urban experience, allowing the observer to map the unique environmental features of a specific place. Regarding the settlement development of the last two centuries, it can be stated that Europe-wide the engineering disciplines dominate the field of urban planning. A significant role is given to architects, which naturally further increases with mass construction projects. Besides architectural considerations, by the turn of the 20th centuries landscape architecture emerges with such ideas as the Garden city movement (Ebenezer-Howard, Unwinn in England, the City Beautiful in the United States etc.) Somewhat later, in the first half of the 2oth century the ubiquitous economical and reál estate aspects start to influence the complex process of urban planning.